Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper provides a semi-annual review of the status of financing for PRGF-ESF lending, HIPC and MDRI debt relief, and subsidization of emergency assistance to PRGF-eligible members. The last review was completed by the Executive Board on September 6, 2006.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet